A PARTICIPATORY ADMINISTRATION MODEL ACCORDANCE TO APARIHANIYADHAMMA OF SUB-DISTRICT MUNICIPALITY SURIN PROVINCE - ญาณธโร (จันทึก) พระสุระ (Journal of MCU Social Science Review, 2020)
The objectives of this research were: 1. to study the general condition of participation administration of sub-district municipality in Surin Province, 2. to study concept and theory related to participation administration and Dhamma used for administration and 3. to propose a model of participation administration in according to Apparihaniyadhamma of sub-district municipality in Surin Province. Methodology was the mixed methods. The quantitative research collected data with questionnaires with the reliability coefficient value at 0.933 from 327 samples who were personnel at sub-district municipality in Surin Province by stratified random sampling, analyzed data with frequency, percentile, mean and standard deviation. The qualitative research collected data from 26 key informants by in-depth-interview and from 10 participants in focus group discussion and analyzed data by descriptive interpretation. Findings were as follows: 1. General condition of participation administration of sub-district municipality in Surin Province was at high level Each aspects of participation administration were that freedom in administration was at high level core objectives and target was at high level obligation at trust each other was at low level at 2. Concepts and theory related to participation administration of subdistrict municipality in Surin Province was the participation in 4 areas; 1) trustworthiness, 2) obligation, 3) core target and objectives, 4) freedom in job performance applying the Apparihaniyadhamma; 1) regular meeting, 2) meeting together, adjournment together 3) not to establish new rules or to abolish the well established rules as one likes.4) respect elders and supervisors, 5) honoring and protecting women and children, 6) protect and conserve the good and invaluable traditions and cultures, 7) righteous protection. 3. Models of participation administration of sub-district municipality in Surin Province was of 4 models. They were 1) a model of trust according Apparihaniyadhamma of sub-district municipality in Surin Province, 2) a model of commitment according Apparihaniyadhamma of sub-district municipality in Surin Province, 3) a model of target and objectives according Apparihaniyadhamma of sub-district municipality in Surin Province, 4) a model of freedom to perform duties according Apparihaniyadhamma of sub-district municipality in Surin Province. Each model has 3 levels; 1) personal level, 2) operational level, 3) administrative level with 12 components; (1) knowledge with ethics, (2) promptness, (3) total responsibility, (4) good human relations, (5) unity, harmony and conciliation, (6) Dhamma leads organizations, (7) well discipline with balance livelihood, (8) performing duties by unanimous agreement, (9) Dhammadipataya, Righteous rules, (10) good consciousness toward society, (11) performing duties with capacity for efficiency, (12) principles of good governance.